Incidence of ATRX mutations in myelodysplastic syndromes, the value of microcytosis. Issue 8 (August 2015) - Herbaux, Charles; Duployez, Nicolas; Badens, Catherine; Poret, Nicolas; Gardin, Claude; Decamp, Mathieu; Eclache, Virginie; Daliphard, Sylvie; Murati, Anne; Cony‐Makhoul, Pascale; Cheze, Stéphane; Beve, Blandine; et al.
<x xml:space="preserve">Abstract</x> Acquired α‐thalassemia myelodysplastic syndrome (MDS) (ATMDS) is an acquired syndrome characterized by a somatic point mutation or splicing defect in the ATRX gene in patients with myeloid disorders, primarily MDS. In a large MDS patient series, the incidence of ATMDS was below 0.5%. But no large series has yet assessed the incidence of ATMDS in microcytic MDS. In this study, we focused on patients with MDS and unexplained microcytosis, which was defined as absence of iron deficiency, inflammatory disease, or history of inherited hemoglobinopathy. Our data confirm the low frequency of ATRX mutations in MDS: 0% in an unselected clinical trial cohort of 80 low risk MDS, 0.2–0.8% in a multicenter registry of 2, 980 MDS and 43% of MDS with unexplained microcytosis in this same registry. In addition, we reported four novel mutations of the ATRX gene in ATMDS. This study further determines the frequency of ATRX mutations and highlights the importance of microcytosis to detect ATRX mutations within MDS patients. Am. J. Hematol. 90:737–738, 2015. © 2015 Wiley Periodicals, Inc.